"Abdominal panniculectomy: Identifying complications and potential risk factors". Issue 9 (September 2022) - Samuel, Ankhita R.; Hakami, Lee; Campbell, Christopher; DeGeorge Jr, Brent R.; Black, Jonathan; Stranix, John T.
Summary: Background: The abdominal panniculectomy is a common procedure that patients choose to undergo for the purpose of restoring hygiene, reducing infection, and improving personal esthetic. A panniculectomy is often indicated after bariatric surgery, which defines a high-risk patient population. This study sought to better establish the association of known risk factors that can complicate the postoperative care of the panniculectomy patient, and whether or not bariatric surgery plays a role in the development of these complications. Methods: Patients that underwent a panniculectomy between 2010 and 2018 were identified in PearlDiver, a national insurance-claims database, and identified by CPT code 15, 380. Patient demographics and associated medical problems were elucidated, and various complications were then identified. Descriptive statistics as well as a multivariate analysis were used to evaluate the association of risk factors and complications. Results: A total of 8, 282 panniculectomy patients were identified. Of these, 1, 420 underwent bariatric weight loss surgery prior to their panniculectomy, whereas the remaining 6, 869 underwent a panniculectomy alone. Obesity, tobacco use, and diabetes were significant in developing a surgical site infection, wound disruption, and the need to undergo reoperation. Charlson Comorbidity Index greater than one (CCI>1), male gender, age greater than 60, COPD, and HTN identified as potential risk factors in developing various complications. Although patients with prior weight loss surgery had a history significant for prior comorbidities, the overall postoperative complication rate was decreased compared to those who did not undergo preoperative bariatric surgery. Conclusion: In the face of the obesity epidemic, the incidence of undergoing a panniculectomy has increased significantly, particularly following bariatric surgery. Identifying potential risk factors in this patient population could better help identify postoperative complications following a panniculectomy and perhaps allow for targeted intervention and medical optimization prior to surgery.